Visual and Ocular Characteristics of eSports Participants. Issue 7 (July 2021) - Fogt, Jennifer Swingle; Onate, James; Emerson, Angela; Kraemer, William; Fogt, Nick
Abstract : SIGNIFICANCE: The popularity of competitive video game play is growing rapidly. Little is known about the ocular characteristics of esports participants. Refractive error and binocular measures in young adult gamers were similar to population norms. However, tear breakup time was lower, and accommodative lag was higher. PURPOSE: In a recent report, very young video game players were found to have greater levels of refractive error and heterophoria and reduced stereopsis. The purpose of this study was to assess the visual and ocular characteristics of a group of recreational esports athletes to determine if the findings in young children were similar to findings in a group of young adult video game players. METHODS: Vision tests were performed on 36 college students during a video game combine event. Testing included high- and low-contrast visual acuity, autorefraction at distance and at 33 cm, stereoacuity, near heterophoria, and tear breakup time. Participants also indicated their level or rank in the game Overwatch. RESULTS: Fifteen participants were myopic, and 21 did not wear vision correction. The mean local stereopsis was 31.9 seconds. The mean of the esophoric value was 3.2 prism diopters, and the mean of the exophoric value was 5.7 prism diopters. The mean lag of accommodation was 0.81 D. The mean tear breakup time was 5.8 seconds. Average hours of play did not differ between those who wore vision correction and those who did not. There were no significant relationships between the hours of play and the ocular findings. CONCLUSIONS: The prevalence of refractive error and the mean heterophoria were similar to population norms, and the mean stereoacuity was normal. However, accommodative lag was slightly higher, and the tear breakup time was lower than expected. Differences in these latter values were also noted between high- and low-level Overwatch players.